AN INTERLANGUAGE ERROR ANALYSIS: A FORMATIVE EVALUATION FOR FRESHMEN - Tiarina, Yuli (English Department FBS UNP, 2017)
This paper aims at finding the interlanguage errors made by the freshmen of English Department of Universitas Negeri Padang. This research needs to be conducted since the result can become a formative evaluation for lecturers in teaching English for the freshmen. The method used in this reserach is a qualitative-descriptive method, supported by simple quantitative calculation. The data were taken from students’ mid term examination. The mid term examination included multiple choice, cloze procedure and composition or writing test. In writing test, the students were asked to write a one-paragrah composition. There were 6 (six) classes participaed in the test. One class was randomly taken as a sample A Target Modification Taxonomy by James (1998) is used to analyze and describe the errors. It analyzes what types of errors made most by the subject of this study. It was found that the most commonly made interlanguage errors by the freshmen are omission.Key words: Error analysis; Interlanguage; Target Modification Taxonomy; ANALISA KESALAHAN INTERLANGUAGE: EVALUASI FORMATIF UNTUK MAHASISWA TAHUN PERTAMAAbstrakArtikel ini bertujuan untuk menemukan kesalahan interlanguage yang dibuat oleh mahasiswa baru atau tahun pertama Jurusan Bahasa Inggris Universitas Negeri Padang. Penelitian ini perlu dilakukan karena hasil darai penelitian ini bisa dijadikan sebagai evaluasi formatif dari dosen untuk mahasiswa tahun pertama. Penelitian ini adalah penelitian deskriptif kualitatif, didukung oleh perhitungan kuantitatif sederhana. Data berasal dari nilai ujian tengah semester mahasiswa. Jenis tes yang digunakan adalah pilihan ganda, melengkapi kalimat rumpang dan ujian menulis. Dalam ujian menulis, mahasiswa diminta untuk menulis satu buah paragraf. Ada 6 (enam) kelas yang terlibat dalam penelitian ini. Satu kelas diambil sebagai kelas sampel. Target Modification Taxonomy oleh James (1998) digunakan dalam menganalisa dan mendiskripsikan jenis kesalahan yang dibuat oleh mahasiswa. Penelitian ini menemukan bahwa jenis kesalahan yang paling banyak dibuat oleh mahasiswa adalah omission.Kata Kunci: Error analysis; Interlanguage; Target Modification Taxonomy;